Duoethnography for Reconciliation: Learning through Conversations - MacDonald, Jennifer; Markides, Jennifer (Alberta Journal of Educational Research, 2019)
Positioned by our different cultural backgrounds and histories, we come together as educators to form an ethical space of engagement to discuss the complexities of truth and reconciliation in Canada. As an opening for our dialogue, we reflect on our earlier research—a duoethnographic reading of the Truth and Reconciliation Commission’s 94 Calls to Action. We came to this work with little prior knowledge, and mixed feelings of nervousness, reverence, and responsibility. By sharing our journey, we may offer direction and support for others interested in beginning or furthering their own reconciliatory journeys. We invite readers to join in our conversations around coming together, negotiating collective responsibilities, making space for dialogue, and creating safety for making mistakes. As we walk together, we see this as a complex opening of possibilities, which requires continuous and simultaneous circling back and circling forward. Positionnées par nos milieux et nos antécédents culturels différents, nous nous retrouvons ensemble comme enseignantes pour former un espace éthique où discuter des complexités de la vérité et réconciliation au Canada. En guise de début de dialogue, nous réfléchissons sur notre recherche antérieure, une lecture duo-ethnographique des 94 appels à l’action de la Commission de vérité et réconciliation. Quand nous avons commencé ce travail, nous avions peu de connaissances antérieures et ressentions à la fois de la nervosité, de la révérence et un sens de responsabilité. En partageant notre parcours, nous espérons orienter et appuyer ceux et celles qui s’intéresseraient à entamer ou poursuivre leur propre processus de réconciliation. Nous invitons les lecteurs à se joindre à nos conversations portant sur le rassemblement, la négociation de responsabilités collectives, et l’établissement d’un d’espace pour le dialogue où les gens se sentent à l’aise de commettre des erreurs. En se déplaçant ensemble, nous entrevoyons des possibilités complexes qui exigent des mouvements continus et simultanés vers l’avant et l’arrière. Mots clés : réconciliation; duo-ethnographie; appels à l’action; éducation, parcours de vie